Climate Change and Social-ecological Vulnerability in the Himalaya: A Study of the Kaligandaki Basin, Nepal - Pandey, Rishikesh (Dhaulagiri Journal of Sociology and Anthropology, 2024)
This research examines the implications and opportunities for climate change adaptation in the Kaligandaki Basin, Nepali Himalaya. The study adopts a holistic approach to explain human-environmental interrelationships. The Sustainable Livelihood Approach and the system approach of analyzing Change-Impact-Response are integrated to construct a dynamic framework that assesses household and sub-regional social-ecological vulnerability. Findings suggest that climate-sensitive social-ecological systems of the Himalayas are highly exposed to both climate change and non-climatic stressors. Households are trying to adapt to rapid change; however, their adaptation knowledge is not sufficiently translated into actions. Consequently, food and livelihood systems are insecure, and social ecosystems in the Basin are highly vulnerable to change.